The Values of Female Character Education in the Millennial Generation Through Suntiang Nan Salapan - Efrita Norman; Ismail Mustaqim; Siti Aminah (Jurnal Dirosah Islamiyah, 2022)
Suntiang Gadang is a bride's headdress in Minangkabau. Visually, Suntiang has a very attractive appearance, apart from its color, it is also supported by the variety of decorations arranged in it. The ornamental variety is taken from natural forms which are grouped into the form of plant motifs and animal motifs. The diversity of decorations found in suntiang not only aims to give beauty and beauty to the person, it also contains moral messages aimed at the bride and groom and will be role models in domestic life. Based on the results of this study, we can draw the following conclusions: that with the rapid growth of technology and information that can be accessed by our millennial generation, it is fitting for us to maintain and develop the customs and cultures that exist in Indonesia, one of which is Minangkabau culture. dense with values ​​and character education, especially for mothers and especially millennial women that we can explore, one of which is in Suntiang Nan Salapan, where in Suntiang Nan Salapan there are character values, including: (1) Minang women must be the pillars of life. the household must be calm and do not like to visit and gossip (2) The woman must be able to arrange the house so that the household is beautiful and comfortable so that the husband feels at home (3) The woman must be able to keep and preserve the things in the household ( 4) Women must be able to manage their finances price so that (5) women must be skilled when they come down to society, because in mainang kabau it is famous for the term bundo kanduang, where women's voices are very much taken into account (6) women must be role models for generations and generations (7) women must be able to educate their offspring with a gentle valley (8) and women are able to guide their people to do amar makruh nahi munkar Keywords: character building, Suntiang Nan Salapan, millennial generation